Field notes contributed by Thomas J. Staudt, spring 1982 - Staudt, Thomas J.et al (1982)
Field notes were contributed by Thomas J. Staudt. This item was used as supporting documentation for the Iowa Ornithologists' Union Quarterly field report of spring 1982. Epson - sheet feed